Whole-Genome Sequencing of Seven Strains of Staphylococcus lugdunensis Allows Identification of Mobile Genetic Elements. (1st May 2017) - Argemi, Xavier; Martin, Véronique; Loux, Valentin; Dahyot, Sandrine; Lebeurre, Jérémie; Guffroy, Aurélien; Martin, Mickael; Velay, Aurélie; Keller, Daniel; Riegel, Philippe; Hansmann, Yves; Paul, Nicodème; et al.
Abstract : Coagulase negative staphylococci are normal inhabitant of the human skin flora that account for an increasing number of infections, particularly hospital-acquired infections. Staphylococcus lugdunensis has emerged as a most virulent species causing various infections with clinical characteristics close to what clinicians usually observe with Staphylococcus aureus and both bacteria share more than 70% of their genome. Virulence of S. aureus relies on a large repertoire of virulence factors, many of which are encoded on mobile genetic elements. S. lugdunensis also bears various putative virulence genes but only one complete genome with extensive analysis has been published with one prophage sequence (φSL2) and a unique plasmid was previously described. In this study, we performed de novo sequencing, whole genome assembly and annotation of seven strains of S. lugdunensis from VISLISI clinical trial. We searched for the presence of virulence genes and mobile genetics elements using bioinformatics tools. We identified four new prophages, named φSL2 to φSL4, belonging to the Siphoviridae class and five plasmids, named pVISLISI_1 to pVISLISI_5 . Three plasmids are homologous to known plasmids that include, amongst others, one S. aureus plasmid. The two other plasmids were not described previously. This study provides a new context for the study of S. lugdunensis virulence suggesting the occurrence of several genetic recombination' with other staphylococci.